The Twelfth International Symposium on High-Performance Computer Architecture, 2006.
DOI: 10.1109/hpca.2006.1598120
|View full text |Cite
|
Sign up to set email alerts
|

DMA-Aware Memory Energy Management

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 16 publications
(39 reference statements)
0
60
0
Order By: Relevance
“…Early works on reducing DRAM background power propose hardware and software policies for switching to low power DRAM modes [3][4][5][6], [18]. Our techniques further reduce DRAM background by servicing most of the required refreshes in the lowest power mode.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Early works on reducing DRAM background power propose hardware and software policies for switching to low power DRAM modes [3][4][5][6], [18]. Our techniques further reduce DRAM background by servicing most of the required refreshes in the lowest power mode.…”
Section: Related Workmentioning
confidence: 99%
“…For example, in the deepest low power Self Refresh (SR) mode, the entire clocked DRAM circuitry is turned off, resulting in no additional power dissipation beyond the power required to refresh the DRAM cells. Many previous papers have proposed intelligent schemes to utilize these low power modes to save DRAM power [3][4][5][6][7][8]. The key idea behind these schemes is to switch a DRAM rank to a lower power mode whenever the rank stays idle for a time period longer than a pre-determined threshold.…”
Section: Introductionmentioning
confidence: 99%
“…As with processors, idle low-power states (e.g., precharge powerdown, self-refresh) have been extensively studied, e.g. [11,22,27,28,34]. However, past work has shown that active lowpower modes are more successful at garnering energy savings for server workloads [9,10,31].…”
Section: Memory Power Managementmentioning
confidence: 99%
“…Performance management. Similar to the approach initially proposed in [28] and later explored in [9,10,11,34], our policy is based on the notion of program slack: the difference between a baseline execution and a target latency penalty that a system operator is willing to incur on a program to save energy. The basic idea is that energy management often necessitates running the target program with reduced core or memory subsystem performance.…”
Section: Coscalementioning
confidence: 99%
See 1 more Smart Citation